O tráfico de pessoas no contexto da exploração econômica neocolonial: dilemas, ações e solidariedade na região da tríplice fronteira (Argentina-Brasil-Paraguai) - Patruni, Anna Paula Cardoso de Paula (2018)
Trafficking in persons has now turned out to be one of the most barbarous forms of abuse and violence against the dignity of the human person. Large criminal organizations act transnationally to perpetuate the economic exploitation of human life, using all forms and practices that offend human dignity and the value of work. Taking as a starting point the origin of human trafficking, under the focus of the grooming of black women, can be identified the modification, over the last centuries, to the current level and difficult to control by state organs to combat human trafficking, which affects men, women, adolescents and children indiscriminately. The national state and Brazilian organized civil society in the last decade have intensified the issue of public coping policies. More severe laws to combat crime have led to some institutional adjustments that, although they have made it difficult for criminals to act, have not achieved the expected effectiveness. In particular, they have been unable to cope with vulnerability that weaken victims by facilitating favoring networks, often disguised as legally established companies, in the enticement of human labor. Adopting the action-research method through a participant dynamic of research and bibliographic, documentary and action research with the aim of transforming reality where it hopes to demonstrate and justify, with criteria (consistency, consistency and non-contradiction), that the improvement democratic nature makes it possible for both States and civil society to work together to reduce forms of disrespect for human dignity and the freedom of the human person, especially in the context of the tri-border region and in the city of Foz do Iguaçu.